ISOLASI DAN IDENTIFIKASI FLAVONOID PADA DAUN KATU (Sauropus androgynus (L.) Merr) - Wijono, Sri Harsodjo (Makara Journal of Science, 2003)
Isolation and Identification of Flavonoid in Katu Leaf (Sauropus androgynus (L.) Merr. Flavonoids in 95% ethanol extract of katu leaf were isolated using Charaux-Paris method. Extract of 95 % ethanol was fractionated with chloroform, ethyl acetate and three times with n-butanol. Flavonoids to be isolated from n-butanol I fraction by chromatography paper preparative method, and identified by spectrophotometer UV (Ultra-Violet) and infrared. Six flavonoids were isolated, one of flavonoids identified as rutin, and the other five were flavonol OH-3 conjugated or flavon groups.